2021
DOI: 10.1101/2021.01.22.427779
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of Quorum Sensing System inPseudomonas aeruginosaby Psammaplin A and Bisaprasin Isolated from the Marine SpongeAplysinella rhax

Abstract: Natural products isolated from marine sponges have exhibited profound bioactivity and, in some cases, serve as potent quorum sensing inhibitory agents by preventing microbial biofilm formation. In this study, the inhibitory potential of the psammaplin type compounds, psammaplin A (1) and bisaprasin (2), isolated from the marine sponge, Aplysinella rhax, was evaluated in the quorum-sensing inhibitory assay based on the Pseudomonas aeruginosa PAO1 lasB-gfp and P. aeruginosa PAO1 rhlA-gfp biosensor strains. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(67 reference statements)
0
0
0
Order By: Relevance
“…More recently, there have been reviews of bacterial products that include small molecules, enzymes, exopolysaccharides and isolated peptides displaying anti-biofilm activities toward different pathogens [28]. Moreover, several studies have demonstrated solid evidences that plants [29] and marine-derived products [15] are an excellent source to provide abundant natural compounds for the development of preventative and therapeutic agents against biofilm-based infections (Table 1).…”
Section: Anti-biofilm Activity Of Natural Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, there have been reviews of bacterial products that include small molecules, enzymes, exopolysaccharides and isolated peptides displaying anti-biofilm activities toward different pathogens [28]. Moreover, several studies have demonstrated solid evidences that plants [29] and marine-derived products [15] are an excellent source to provide abundant natural compounds for the development of preventative and therapeutic agents against biofilm-based infections (Table 1).…”
Section: Anti-biofilm Activity Of Natural Compoundsmentioning
confidence: 99%
“…Concerning antibiofilm activity of marine-derived products, the study by Oluwabusola et al [15] proved that psammaplin A and bisaprasin, isolated from marine sponges, could be a potent QS inhibitory agents by preventing P. aeruginosa PAO1 biofilm formation. The present results indicated that psammaplin a showed moderate to significant inhibition against QS gene promoters, with IC50 values ranging from 30.69 to 2.64 μM.…”
Section: Anti-biofilm Activity Of Marine and Bacterial-derived Productsmentioning
confidence: 99%